Dopamine polymerization promoted by a catecholase biomimetic CuII(μ-OH)CuII complex containing a triazine-based ligand. Issue 39 (23rd September 2016) - de Oliveira, José A. F.; da Silva, Marcos P.; de Souza, Bernardo; Camargo, Tiago P.; Szpoganicz, Bruno; Neves, Ademir; Bortoluzzi, Adailton J.
Abstract : The catecholase-like catalytic activity and dopamine polymerization by using the dinuclear [LCu II (μ-OH)2 Cu II ](ClO4 )2 (1 ) complex are here described. Abstract : We describe herein the catecholase-like catalytic activity and dopamine polymerization by using a dinuclear [LCu II (μ-OH)2 Cu II ](ClO4 )2 (1 ) complex where L is the dinucleating triazine-based ligand 6-chloro- N 2, N 2, N 4, N 4 -tetrakis(pyridin-2-ylmethyl)-1, 3, 5-triazine-2, 4-diamine. The kinetic parameters ( k cat = 0.318 s −1, K M = 1.6 × 10 −3 mol L −1, and k cat / K M = 198.8 L s −1 mol −1 ), mechanistic insights into the oxidation of 3, 5-di- tert -butyl catechol and early characterization of poly(dopamine) are presented.